Выбор рационального типа автономного источника электропитания для ГРС и ГРП - Моисеев, Александр Николаевич (НТУ "ХПИ", 2013)
Options of independent power supply source for gas-distributing stations and units were reviewed, and their advantages and disadvantages demonstrated. Rational diagrame for independent power supply source with use of turbodetender mechanical power was proposed.
Keywords: магистральные газопроводы; компрессорные станции; газоперекачивающие агрегаты; редуцирующие клапаны; электромеханический комплекс; турбодетандер